The terms 9r^2 and 6r^2 are like terms. We add the numbers to the left of the "r^2" to get 9+6 = 15.
So 9r^2+6r^2 becomes 15r^2
The r^2 stays the same. We do not say something like r^2+r^2 = r^4. You might be thinking of r^2 * r^2 = r^(2+2) = r^4
When it comes to adding like terms, we keep the variables the same.
The other pair of like terms are 3r and 2r, so they add to 3r+2r = 5r
--------------------------------------------------------------------------------------------
Overall,
(9r^2+3r+6)+(6r^2+2r) = (9r^2+6r^2)+(3r+2r)+6
(9r^2+3r+6)+(6r^2+2r) = 15r^2+5r+6